Delivering Dynamic Civics Learning Through the TPACK Approach at the Elementary School Level - Al Fikri, Muhammad Arif (Program Studi Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2026)
This research aims to analyze the implementation of the Technological Pedagogical Content Knowledge (TPACK) approach in creating dynamic Civic Education (PKn) learning at the elementary school level and to identify the challenges educators face. The method used is a Systematic Literature Review (SLR) that reviews 15 selected research articles published between 2020 and 2026. Literature sources were obtained from Google Scholar, DOAJ, SINTA, and Garuda databases using the keywords